2020
DOI: 10.1128/msystems.00495-19
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Basis of Microbial Growth and Persistence in Desert Ecosystems

Abstract: Microbial life is surprisingly abundant and diverse in global desert ecosystems. In these environments, microorganisms endure a multitude of physicochemical stresses, including low water potential, carbon and nitrogen starvation, and extreme temperatures. In this review, we summarize our current understanding of the energetic mechanisms and trophic dynamics that underpin microbial function in desert ecosystems. Accumulating evidence suggests that dormancy is a common strategy that facilitates microbial surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 169 publications
6
62
0
Order By: Relevance
“…Recent studies have shown that the oxidation of atmospheric trace gases can be an alternative energy source for soil microorganisms ( 39 , 68 , 69 ), and it has been hypothesized that it might be widely used to generate maintenance energy during dormancy ( 11 ). We detected MAGs with the potential for H 2 oxidation in the phyla Actinobacteriota and Chloroflexota , consistent with previous investigations ( 70 ), and H 2 oxidation was recently detected in BSCs from the same sampling site ( 133 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the oxidation of atmospheric trace gases can be an alternative energy source for soil microorganisms ( 39 , 68 , 69 ), and it has been hypothesized that it might be widely used to generate maintenance energy during dormancy ( 11 ). We detected MAGs with the potential for H 2 oxidation in the phyla Actinobacteriota and Chloroflexota , consistent with previous investigations ( 70 ), and H 2 oxidation was recently detected in BSCs from the same sampling site ( 133 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, dryland soils are inhabited by a variety of other microbial clades ( 3 , 10 ) whose mechanisms of surviving desiccation are unknown. It was recently suggested that many soil microorganisms might rely on inorganic energy sources such as light and oxidation of atmospheric trace gases (e.g., dihydrogen [H 2 ] and carbon monoxide [CO]) to maintain the cell’s integrity in a dormant state ( 11 ). Furthermore, trace gas oxidation could potentially support primary production, as oxidation of atmospheric H 2 has been shown to sustain CO 2 fixation in an Antarctic desert soil ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drought limits the abundance and productivity of oxygenic photoautotrophs, namely, cyanobacteria, microalgae, and plants, which require water as an electron donor. Low supplies of organic carbon, combined with impaired substrate diffusion and membrane transport, in turn limit the abundance of chemoheterotrophic microorganisms and fauna ( 6 , 7 ). The extents of nutrient limitation vary: semiarid deserts experience considerable precipitation and subsequent productivity, albeit counterbalanced by evapotranspiration, whereas hyperarid deserts can be deprived of rainfall over decadal scales ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…KEYWORDS carbon fixation, desert, hydrogen, hydrogenase, primary production, trace gas S panning a third of land surfaces, deserts are extensive terrestrial biomes that are expanding due to multiple anthropogenic pressures (1,2). Organisms residing in these ecosystems endure severe and prolonged drought interspersed with infrequent hydration pulses, often in combination with other physicochemical pressures (3)(4)(5)(6). Drought limits the abundance and productivity of oxygenic photoautotrophs, namely, cyanobacteria, microalgae, and plants, which require water as an electron donor.…”
mentioning
confidence: 99%
See 1 more Smart Citation